Motor Neuron Syndrome as a New Phenotypic Manifestation of Mutation 9185T>C in Gene MTATP6 - Marisa Brum; Cristina Semedo; Rui Guerreiro; José Pinto Marques (Case Reports in Neurological Medicine)
Background. The mutation 9185T>C in ATP6 gene, associated with Leigh syndrome, was reported in only few families. Motor neuron disease (MND), both clinically and electrophysiologically, was not previously described in association with this mutation. Case Report. 33-year-old male, with family history of mitochondrial disease, presented with cognitive impairment, exercise intolerance, and progressive muscle weakness. Examination revealed global hypotonia, and proximal tetraparesis, without atrophy or fasciculation, pyramidal signs, or sensory symptoms. The laboratory findings revealed an increase of lactate and lactate/pyruvate ratio; electromyogram showed chronic neurogenic compromise; muscle biopsy was suggestive of spinal muscular atrophy and mitochondriopathy; genetic study of SMN1 was negative but detected a homoplasmic mutation 9185T>C in ATP6 gene. His younger sister, with the same mutation, had cognitive impairment, ataxia, and muscle weakness. EMG showed axonal peripheral neuropathy. Conclusion. This case is unique because of the benignity and the coexistence of clinical, neurophysiological, and pathological findings suggestive of MND that, although described in mitochondrial disease, have not yet been reported in association with 9185T>C mutation. The present case contributes to the expansion of the phenotypic expressions of this particular mutation.